Monstrosity and Chinese cultural identity - Yue, Isaac (Cambria Press, 2020)
China turning inward: Foreignness and otherness in the development of Chinese cultural identity – Bestiality and brutality: The imagination of foreigners as uncivilized animals – The barbarian and/as the hero: The case of Zhang Fei – The taming of the ape: A Chinese sutra – An animalistic warrior? A demon-vanquishing scholar?: The two faces of Zhong Kui – Conclusion.
Includes bibliographical references and index
Keywords: Chinese literature; Xenophobia in literature; Aliens in literature; Other (Philosophy) in literature; Animals in literature; Monsters in literature